Pengembangan Tes Literasi Sains Berkonteks Socio-Scientific Issues (SSI) untuk Siswa SMP - Rai Putri Diantari; I Nyoman Tika; Ni Made Wiratini (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop a scientific literacy test with an SSI context to measure the scientific literacy skills of junior high school students. This study refers to the design research model by Plomp and Nieven, consisting of preliminary research, development or prototyping phase, and evaluation phase. This research is limited to the development phase. In the preliminary study phase, needs analysis, context analysis, preparation of the initial test design, test item development, test validation, and revision were conducted. In the development phase, a limited trial was conducted to evaluate the test's practicality and a field trial to evaluate item validity, discriminatory power, distractor quality, and test reliability. The developed test is in the form of multiple-choice items with 4 answer options. The scientific literacy competencies measured in the test refer to the PISA 2025 framework. A total of 10 SSI issues relevant to the science material of phase D of the independent curriculum were used as question stimuli. Expert validation was analyzed using Gregory obtained a score of 1.00 indicating the test has very high validity in terms of content, construct, and language. The test is in the very practical category. The field trial involved 100 ninth-grade students. The item validity results showed 28 valid items and 2 invalid items. The discrimination index of all items met the good criteria. All distractors in each item were accepted and functional. The reliability of the test script was 0.911, which is in the very good category. These results indicate that the test can be used to measure the scientific literacy skills of junior high school students.